Improving Science Process Skill in Science Subject in Elementary School - Siagian, Novia G.; Wardani, Sri; Widiarti, Nuni; Yuwono, Agus (Journal of Learning Improvement and Lesson Study, 2025)
Science process skills (SPS) are essential to be developed from the elementary level to foster students' critical and scientific thinking abilities. This study is a literature review of 20 national and international scientific articles published between 2020 and 2025. The method used is a qualitative and quantitative analysis to examine effective learning approaches for improving SPS. The findings indicate that discovery learning, ethno-STEM, simple experiments, and inquiry-based learning significantly enhance SPS. The study concludes that active and contextual learning strategies are crucial for developing SPS in elementary school students.